Frequency and Factors Associated With Honorary Authorship in Indian Biomedical Journals: Analysis of Papers Published From 2012 to 2013. (April 2018) - Shah, Akash; Rajasekaran, Sathish; Bhat, Anup; Solomon, John M.
Honorary authorship is the inclusion of an author on an article whose contribution does not warrant authorship. We conducted an Internet-based survey among first authors publishing in Indian biomedical journals from 2012 to 2013 to study the frequency and factors associated with honorary authorship. The response rate was 27% (245/908) with the prevalence of perceived, International Committee of Medical Journal Editors (ICMJE)-defined, and unperceived honorary authorship of 20.9% (50/239), 60% (147/245), and 46.9% (115/245), respectively. Those residing in India were found to list more honorary authors. We hope to increase awareness of the ICMJE authorship guidelines and the general issue of honorary authorship among researchers in India and elsewhere.